Skin Tissue Substitutes and Biomaterial Risk Assessment and Testing - Savoji, Houman; Godau, Brent; Hassani, Mohsen Sheikh; Akbari, Mohsen (Frontiers in Bioengineering and Biotechnology, 2018)
Tremendous progress has been made over the past few decades to develop skin substitutes management of acute and chronic wounds. With the advent of tissue engineering and the ability to combine advanced manufacturing technologies with biomaterials and cell culture systems, more biomimetic tissue constructs have been emerged. Synthetic and natural biomaterials are the main constituents of these skin-like constructs, which play a significant role in the tissue grafting, the body’s immune respond, and the healing process. The act of implanting biomaterials into the human body is subject to the body’s immune response, and the complex nature of the immune system involves many different cell types and biological processes that will ultimately determine the success of a skin implant. As such, a large body of recent studies has been focused on the evaluation of the performance and risk assessment of these substitutes. This review summarizes the past and present advances in in vitro, in vivo and clinical applications of tissue-engineered skin. We discuss the role of immunomodulatory biomaterials and biomaterials risk assessment in skin tissue engineering. We will finally offer a roadmap for regulating tissue engineered skin substitutes.